The role of circTmeff-1 in incubation of context-induced morphine craving. (August 2021) - Yu, Hailei; Xie, Bing; Zhang, Jingjing; Luo, Yixiao; Galaj, Ewa; Zhang, Xiuning; Shen, Qianchao; Liu, Yi; Cong, Bin; Wen, Di; Ma, Chunling
Abstract: A progressive increase in drug craving following drug exposure is an important trigger of relapse. CircularRNAs (CircRNAs), key regulators of gene expression, play an important role in neurological diseases. However, the role of circRNAs in drug craving is unclear. In the present study, we trained mice to morphine conditioned place preference (CPP) and collected the nucleus accumbens (NAc) sections on abstinence day 1 (AD1) and day 14 (AD14) for RNA-sequencing. CircTmeff-1, which was highly expressed in the NAc core, was associated with incubation of context-induced morphine craving. The gain- and loss- of function showed that circTmeff-1 was a positive regulator of incubation. Simultaneously, the expression of miR-541–5p and miR-6934–3p were down-regulated in the NAc core during the incubation period. The dual luciferase reporter, RNA pulldown, and fluorescence insitu hybridization assays confirmed that miR-541–5p and miR-6934–3p bind to circTmeff-1 selectively. Furthermore, bioinformatics and western blot analysis suggested that vesicle-associated membrane protein 1 (VAMP1) and neurofascin (NFASC), both overlapping targets of miR-541–5p and miR-6934–3p, were highly expressed during incubation. Lastly, AAV-induced down-regulation of circTmeff-1 decreased VAMP1 and NFASC expression and incubation of morphine craving. These findings suggested that circTmeff-1, a novel circRNA, promotes incubation of context-induced morphine craving by sponging miR-541/miR-6934 in the NAc core. Thus, circTmeff-1 represents a potential therapeutic target for context-induced opioid craving, following prolonged abstinence. Graphical Abstract: ga1